1994
DOI: 10.1113/expphysiol.1994.sp003745
|View full text |Cite
|
Sign up to set email alerts
|

Role of prostaglandins in regulation of blood flow and modulation of sympathetic vasoconstriction in normal and acutely inflamed rabbit knee joints

Abstract: SUMMARYExperiments were performed to investigate, in the normal and acutely inflamed rabbit knee joint, the role of prostaglandins in the regulation ofjoint blood flow, measured b) laser Doppler flowmetry, as well as their modulation of sympathetic vasoconstriction. Close intra-arterial injection of prostaglandin E2 (PGE2) produced a dose-dependent vasodilatation in control joints, but the responses in inflamed joints were much smaller. Close intra-arterial infusion of indomethacin significantly increased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…This is supported by the fact that vascular resistance is increased by equimolar infusions (0.34 nmol min _1 ) of a non-selective COX inhibitor, but not a selective COX-2 inhibitor, and further by the detection of COX-1 but not COX-2 mRNA in joint tissue. These findings corroborate an earlier study on the rabbit knee by Najafipour & Ferrell (1994), and extend their work by using a more physiological preparation, more appropriate laser Doppler technology and by expanding the investigation to examine the roles of COX-1 and COX-2. The latter was achieved by using the novel selective COX-2 inhibitor, SC-236, and by investigating COX-1 and COX-2 expression using RT-PCR.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is supported by the fact that vascular resistance is increased by equimolar infusions (0.34 nmol min _1 ) of a non-selective COX inhibitor, but not a selective COX-2 inhibitor, and further by the detection of COX-1 but not COX-2 mRNA in joint tissue. These findings corroborate an earlier study on the rabbit knee by Najafipour & Ferrell (1994), and extend their work by using a more physiological preparation, more appropriate laser Doppler technology and by expanding the investigation to examine the roles of COX-1 and COX-2. The latter was achieved by using the novel selective COX-2 inhibitor, SC-236, and by investigating COX-1 and COX-2 expression using RT-PCR.…”
Section: Discussionsupporting
confidence: 87%
“…The LDI technique as used in the present study has many advantages over the laser Doppler flowmeter used by Najafipour & Ferrell (1994). Essentially it enables the sampling of an area of tissue in a relatively short time frame, thereby allowing the spatial distribution of tissue perfusion to be mapped.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study showed a significant reduction in the efficacy of the sympathetic nervous system in regulating blood flow to the inflamed joint (Najafipour & Ferrell, 1995), a possible explanation for the significantly higher blood flow observed in this condition. Further investigations revealed that although prostaglandins have a role to play in the regulation of basal blood flow to the inflamed joint but they do not appear to play a significant role in the modulation of sympathetic vasoconstriction responses (Najafipour & Ferrell, 1994). Also, nitric oxide (NO) production does not appear to be changed by the process of acute inflammation (Najafipour & Ferrell, 1993b).…”
mentioning
confidence: 99%
“…Blood-vessel response to saphenous nerve stimulation was also shown to be reduced in chronically inflamed rat knee joints [15]. Further investigation revealed that although prostaglandins have a role to play in the regulation of basal blood flow to the inflamed joint, they do not appear to play a significant role in the modulation of sympathetic vasoconstriction response [21]. Also, nitric oxide (NO) production did not appear to be changed by the process of acute inflammation in the joint [18].…”
Section: Introductionmentioning
confidence: 97%